The Masorah of Elijah ha-Naqdan: an edition of Ashkenazic micrographical notes - Attia, Élodie (Materiale Textkulturen, 2015)
This volume is the first attempt to critically edit the textual contents of Masoretic notes written in micrographical designs. Within this pioneer work, Élodie Attia focuses on the Masorah of a 13th-century Northern French scribe, Elijah ben Berechiah ha-Naqdan (alive in 1233–1239), and provides new evidence about the transmission of Biblical and Masoretic knowledge in Western Europe and in Ashkenaz.
Keywords: Elijah ben Berechiah -- ha-Naqdan -- active 13th century -- Knowledge -- Masorah; Biblioteca apostolica vaticana -- Manuscript -- Vat. ebr. 14; Bible -- Exodus -- Selections -- Criticism, Textual; Geschichte; Kalligrafie; Bibel / Altes Testament; Hebräisch; Schriftkunst; Bibel / Exodus; Elijah ben Berechiah <ha-Naqdan>